From seed to sapling: effects of plant community, soil cover and fire in the recruitment and establishment of maritime pine - Rodrigues, Diana Manuela Antunes (2021)
Pinus pinaster forests are among the most affected forests by fire in the Mediterranean. The main objective of this dissertation was to study the natural dynamics of P. pinaster natural regeneration in a post-fire scenario in three populations of central coastal Portugal, that affected by the 2017 fires (our treatment). For this, 18 sampling points with two replicas, areas of 50m2 were sampled, in which forest stands and understory vegetation structures were characterized. The density of P. pinaster regeneration was assessed in four sub-plots of 1m2 in each treatment and population. ANOVAs were performed to verify differences between populations and treatments. Correlations between maritime pine regeneration and the study variables: biotic (stand, soil cover and plant cover) and abiotic (topography and climate), were tested by calculating Spearman correlations. Regeneration values considered sustainable were recorded in all three populations for the two treatments, where only Mira showed signs of establishment difficulty due to low survival rates. Older stands, with higher biomass productions, show a negative relationship with survival and height of regeneration. High levels of invasion were recorded which showed a negative relationship with regeneration density and survival. The height of the invasive cover demonstrated to be negative for survival, thus demonstrating in both cases relations of competition. The opposite effect was verified for the cover of native flora where positive relations were registered with survival and height of regeneration, thus demonstrating relations of facilitation with regeneration.